Dispute management in construction industry - Chai, Chang Sa'ar (2009)
Construction industry is one of the important contributors to the national development. However, construction industry had been plagued due to the complexity and fragmented process which lead to dispute situation. Hence, the objectives of this study are to review the dispute management in construction industry, to analyze the perceive importance of factors contribute to disputes, to evaluate the contractual methods in dispute avoidance and resolutions, and to develop a framework of dispute avoidance and resolution in variation factor. 30 sets of questionnaires delivered to the expert who actively involved in dealing conflicts and disputes. The study identified 30 factors as the major factors leading to construction dispute. Among the factors, change orders and delay had been recognized as the most contributory factors to the construction disputes. From the analysis, negotiation is the most favorable dispute resolution method in construction industry. The study develops a framework of dispute resolution for construction variation factor based on the data collected.